Comparing immunogenicity and protective efficacy of the yellow fever 17D vaccine in mice. Issue 1 (1st January 2021) - Ma, Ji; Boudewijns, Robbert; Sanchez-Felipe, Lorena; Mishra, Niraj; Vercruysse, Thomas; Buh Kum, Dieudonné; Thibaut, Hendrik Jan; Neyts, Johan; Dallmeier, Kai
ABSTRACT: The live-attenuated yellow fever 17D (YF17D) vaccine is one of the most efficacious human vaccines and also employed as a vector for novel vaccines. However, in the lack of appropriate immunocompetent small animal models, mechanistic insight in YF17D-induced protective immunity remains limited. To better understand YF17D vaccination and to identify a suitable mouse model, we evaluated the immunogenicity and protective efficacy of YF17D in five complementary mouse models, i.e. wild-type (WT) BALB/c, C57BL/6, IFN-α/β receptor ( IFNAR -/- ) deficient mice, and in WT mice in which type I IFN signalling was temporally ablated by an IFNAR blocking (MAR-1) antibody. Alike in IFNAR -/- mice, YF17D induced in either WT mice strong humoral immune responses dominated by IgG2a/c isotype (Th1 type) antibodies, yet only when IFNAR was blocked. Vigorous cellular immunity characterized by CD4 + T-cells producing IFN-γ and TNF-α were mounted in MAR-1 treated C57BL/6 and in IFNAR -/- mice. Surprisingly, vaccine-induced protection was largely mouse model dependent. Full protection against lethal intracranial challenge and a massive reduction of virus loads was conferred already by a minimal dose of 2 PFU YF17D in BALB/c and IFNAR -/- mice, but not in C57BL/6 mice. Correlation analysis of infection outcome with pre-challenge immunological markers indicates that YFV-specific IgG might suffice for protection, even in the absence of detectable levels of neutralizing antibodies. Finally, we propose that, in addition to IFNAR -/- mice, C57BL/6 mice with temporally blocked IFN-α/β receptors represent a promising immunocompetent mouse model for the study of YF17D-induced immunity and evaluation of YF17D-derived vaccines.